Chiral separation of dl-glutamic acid by ultrasonic field. Issue 5 (1st December 2016) - Zhou, Xinhui; Wang, Haishui; Zeng, Qiang
Abstract : Thed -glutamic acid crystals can be separated from a racemic solution ofdl -glutamic acid by a typical "in-series enriched method" under an ultrasonic field. Abstract : In this communication, pured - orl -glutamic acid crystals can be obtained from a racemic solution by controllable addition of chiral seed crystals and ultrasonic-assisted recrystallization. In contrast, only racemic compounds were yielded under identical conditions in bulk solutions in the absence of an ultrasonic field.